Ground-state excitation of heavy highly-charged ions. (28th May 2015) - Gumberidze, A; Thorn, D B; Fontes, C J; Najjari, B; Zhang, H L; Surzhykov, A; Voitkiv, A; Fritzsche, S; Banaś, D; Beyer, H; Chen, W; DuBois, R D; et al.
Abstract: We have studied the excitation of H-like and He-like uranium (U 91+ and U 90+ ) in relativistic collisions with gaseous targets by observing the subsequent x-ray emission. The experiment was conducted at the ESR storage ring of the GSI accelerator facility in Darmstadt, Germany. The measurements were performed with a newly developed multi-phase target at different collision energies. This enabled us to explore the proton (nucleus) impact excitation as well as the electron impact excitation processes in the relativistic collisions. The large fine-structure splitting in uranium allowed us to unambiguously resolve excitation to different L-shell levels. Moreover, information about the population of different magnetic sublevels has been obtained via an angular differential study of the decay photons associated with the subsequent de-excitation process. The experimental results are compared with calculations performed within the relativistic framework including excitation mechanisms due to both protons (nucleus) and electrons.